Emerging Standards and the Hybrid Model for Organizing Scientific Events During and After the COVID-19 Pandemic. (26th June 2022) - Hanaei, Sara; Takian, Amirhossein; Majdzadeh, Reza; Maboloc, Christopher Ryan; Grossmann, Igor; Gomes, Orlando; Milosevic, Milos; Gupta, Manoj; Shamshirsaz, Alireza A.; Harbi, Amine; Burhan, Amer M.; Uddin, Lucina Q.; et al.
Abstract: Since the beginning of 2020, the coronavirus disease (COVID-19) pandemic has dramatically influenced almost every aspect of human life. Activities requiring human gatherings have either been postponed, canceled, or held completely virtually. To supplement lack of in-person contact, people have increasingly turned to virtual settings online, advantages of which include increased inclusivity and accessibility and a reduced carbon footprint. However, emerging online technologies cannot fully replace in-person scientific events. In-person meetings are not susceptible to poor Internet connectivity problems, and they provide novel opportunities for socialization, creating new collaborations and sharing ideas. To continue such activities, a hybrid model for scientific events could be a solution offering both in-person and virtual components. While participants can freely choose the mode of their participation, virtual meetings would most benefit those who cannot attend in-person due to the limitations. In-person portions of meetings should be organized with full consideration of prevention and safety strategies, including risk assessment and mitigation, venue and environmental sanitation, participant protection and disease prevention, and promoting the hybrid model. This new way of interaction between scholars can be considered as a part of a resilience system, which was neglected previously and should become a part of routine practice in the scientific community.